Археологічні роботи в Острозі на проспекті Незалежності, 3 - Прищепа, Б.А.; Бондарчук, О.А.; Позіховський, О.Л. (Археологічні дослідження в Україні, 2009)
The publication includes the results of archaeological works in 2007 and 2008 in Ostrih at 3, Nezalezhnosti Avenue. On the area allotted for the construction of the edifice of the National University «Ostrih Academy» the cultural layers and objects of the three periods of development of the settlement were revealed: the Slav-Rus (8th—11th c.), Lithuanian-Polish (16th— 18th c.) periods and the period from the end of the 18th c. to the beginning of the 20 th c.